High‐resolution mapping of sensory fibers at the healthy and post‐myocardial infarct whole transgenic hearts. Issue 3 (14th December 2022) - Sahoglu, Sevilay Goktas; Kazci, Yusuf Enes; Karadogan, Behnaz; Aydin, Mehmet Serif; Nebol, Aylin; Turhan, Mehmet Ugurcan; Ozturk, Gurkan; Cagavi, Esra
Abstract: The sensory nervous system is critical to maintain cardiac function. As opposed to efferent innervation, less is known about cardiac afferents. For this, we mapped the VGLUT2‐expressing cardiac afferent fibers of spinal and vagal origin by using the VGLUT2::tdTomato double transgenic mouse as an approach to visualize the whole hearts both at the dorsal and ventral sides. For comparison, we colabeled mixed‐sex transgenic hearts with either TUJ1 protein for global cardiac innervation or tyrosine hydroxylase for the sympathetic network at the healthy state or following ischemic injury. Interestingly, the nerve density for global and VGLUT2‐expressing afferents was found significantly higher on the dorsal side compared to the ventral side. From the global nerve innervation detected by TUJ1 immunoreactivity, VGLUT2 afferent innervation was detected to be 15–25% of the total network. The detailed characterization of both the atria and the ventricles revealed a remarkable diversity of spinal afferent nerve ending morphologies of flower sprays, intramuscular endings, and end‐net branches that innervate distinct anatomical parts of the heart. Using this integrative approach in a chronic myocardial infarct model, we showed a significant increase in hyperinnervation in the form of axonal sprouts for cardiac afferents at the infarct border zone, as well as denervation at distal sites of the ischemic area. The functional and physiological consequences of the abnormal sensory innervation remodeling post‐ischemic injury should be further evaluated in future studies regarding their potential contribution to cardiac dysfunction. Abstract : The VGLUT2‐expressing cardiac afferent fibers of spinal and vagal origin were mapped by using the VGLUT2::tdTomato double transgenic mouse model. The whole hearts were visualized both at the dorsal and ventral sides. A remarkable diversity of spinal afferent nerve ending morphologies of flower sprays, intramuscular endings, and end‐net branches were shown to innervate distinct anatomical parts of the healthy and post‐MI hearts. Remodeling of cardiac afferents post‐MI was demonstrated for the first time at the border zone and scar area.